2022
DOI: 10.48550/arxiv.2205.03006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoherence from Long-Range Forces in Atom Interferometry

Abstract: Atom interferometers provide a powerful means of realizing quantum coherent systems with increasingly macroscopic extent in space and time. These systems provide an opportunity for a variety of novel tests of fundamental physics, including ultralight dark matter searches and tests of modifications of gravity, using long drop times and microgravity environments. However, as experiments operate with longer periods of free fall and become sensitive to smaller background effects, key questions start to emerge abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…One final caveat we should note: we do not consider any specific backgrounds that could affect these results. A recent study showed that long-distance forces are negligible for decoherence, especially for the short ( 10 s) measurement timescales we consider here [71]. As we discuss in Section II, we expect these processes to be suppressed relative to the light DM models with light mediators.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…One final caveat we should note: we do not consider any specific backgrounds that could affect these results. A recent study showed that long-distance forces are negligible for decoherence, especially for the short ( 10 s) measurement timescales we consider here [71]. As we discuss in Section II, we expect these processes to be suppressed relative to the light DM models with light mediators.…”
Section: Discussionmentioning
confidence: 80%
“…Ref. [71] claimed, via an order of magnitude estimate, that the decoherence between atom clouds caused by cosmic rays are not a significant background. Solar photons, in the forward scattering limit, could be a background source for phase shifts due to their lower energies (which can mimic dark matter kinematics) and high fluxes.…”
Section: Direct Detection With Atom Interferometersmentioning
confidence: 99%